Innovative Approaches in Tourism Business Development - Tatjana Stanovčić; urica Perović; Sanja Peković (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
In order to provide superior experience for tourists, innovative approaches in tourism business and product development are needed. The objective of this paper is to highlight the key challenges in creation of innovative tourism business opportunities, and provide wider understanding of its importance, especially for SMEs. A review of relevant literature on innovations in tourism is undertaken, then focusing on the specific issues in areas of potential forms of innovation. Specialisation, thematisation, inscenation, diversification and resort concept are identified as key innovative opportunities. On the other side, several management and marketing issues are identified regarding mentioned innovative approaches. First of all, competitive tourism environment generates need for cooperative forms of business behaviour, where networking provides additional sources for implementation of innovative initiatives, especially by SMEs. Key benefits of innovations in tourism business are noted and clearly defined, but in the practical sense, these opportunities are still, to a large extent, underused.
Keywords: M21; 330; innovations; tourism; specialisation; diversification